1982
DOI: 10.1016/s0022-5347(17)53509-0
|View full text |Cite
|
Sign up to set email alerts
|

Atropine Resistance of Transmurally Stimulated Isolated Human Bladder Muscle

Abstract: Human detrusor strips were obtained from patients undergoing reimplantation of ureters because of reflux, transvesical prostatectomy, or cysto-urethrectomy en bloc because of bladder malignancy. The strips were electrically stimulated. A frequency-dependent contractant response was obtained that was potentiated by physostigmine and abolished by tetrodotoxin. The maximum response approximately equaled that of acetylcholine in a maximum concentration. In most bladder preparations from patients without known func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
115
0
1

Year Published

1985
1985
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 248 publications
(125 citation statements)
references
References 15 publications
9
115
0
1
Order By: Relevance
“…No significant atropine-resistant neuromuscular transmission was present and in essence all the residual contraction was also resistant to tetrodotoxin, indicating that it was due to direct muscle stimulation rather than nerve stimulation and neurotransmitter release. Atropine virtually eliminates nerveinduced contraction in normal human bladder Sjogren et al, 1982), but noncholinergic nonadrenergic (NANC) neuromuscular communication is present in several other species. Atropine-resistance in humans has been reported in some pathological conditions (Saito et al, 1993;Sjogren et al, 1982), but such findings could actually have been due to direct muscle stimulation.…”
Section: Detrusor Denervation In Spinal Cord Injurymentioning
confidence: 99%
See 2 more Smart Citations
“…No significant atropine-resistant neuromuscular transmission was present and in essence all the residual contraction was also resistant to tetrodotoxin, indicating that it was due to direct muscle stimulation rather than nerve stimulation and neurotransmitter release. Atropine virtually eliminates nerveinduced contraction in normal human bladder Sjogren et al, 1982), but noncholinergic nonadrenergic (NANC) neuromuscular communication is present in several other species. Atropine-resistance in humans has been reported in some pathological conditions (Saito et al, 1993;Sjogren et al, 1982), but such findings could actually have been due to direct muscle stimulation.…”
Section: Detrusor Denervation In Spinal Cord Injurymentioning
confidence: 99%
“…Atropine virtually eliminates nerveinduced contraction in normal human bladder Sjogren et al, 1982), but noncholinergic nonadrenergic (NANC) neuromuscular communication is present in several other species. Atropine-resistance in humans has been reported in some pathological conditions (Saito et al, 1993;Sjogren et al, 1982), but such findings could actually have been due to direct muscle stimulation. NANC neurotransmission may be more prevalent with lowfrequency EFS (Brading and Williams, 1990;Luheshi and Zar, 1990), with the cholinergic component predominating at higher frequencies.…”
Section: Detrusor Denervation In Spinal Cord Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…To date, expression of the pre-proendothelin messenger RNA has been reported only in the vascular endothelium and the potential physiological meaning of these findings is only a matter of speculation. The action of endothelin was substantially atropine-resistant which excludes a significant participation of the cholinergic nerves, the major excitatory innervation of the normal human bladder (Sjogren et al, 1982;Sibley, 1984;Maggi et al, 1988). Further, we found that the action of endothelin is totally resistant to nifedipine at a concentration that abolished the KCI-induced contractions.…”
mentioning
confidence: 99%
“…In the literature dealing with the smooth muscle of the urinary bladder, there is an ongoing discussion about the pathways via which electrical field stimulation Of bladder strips in vitro leads to contraction and whether direct stimulation of the cells is possible (Cowan & Daniel, 1982;Sjogren et al, 1982;Sibley, 1984;Kinder & Mundy, 1985). In this series of experiments, we have shown that single cells contract in response to direct electrical stimulation, provided that the pulse duration is 5.0 ms or longer, and this implies that direct stimulation of bladder strips should be possible.…”
Section: Discussionmentioning
confidence: 99%